The Role of Role Play in Supporting Early Childhood Financial Literacy Development - Marufah Marufah; Rachma Hasibuan; Kartika Rinakit; Nurul Istighfaroh; Mohammad Syaikhul Haq; Andi Kristanto (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
This study aims to describe the influence of the role-play method on financial literacy among early childhood learners. The background of this research stems from the importance of introducing financial understanding at an early age so that children are able to recognize the value of money, distinguish between needs and wants, and learn simple saving practices. This research employed a descriptive qualitative approach with children as the subjects. Data were collected through observations, teacher interviews, and documentation of learning activities. The findings indicate that the implementation of role-play activities such as market day simulations, buying and selling games, and saving simulations can enhance children’s ability to understand the concept of money value, manage money in simple ways, and develop frugal and responsible attitudes. Thus, the role-play method positively influences early childhood financial literacy by providing enjoyable and contextual learning experiences.